Assembly of Aptamer Switch Probes and Photosensitizer on Gold Nanorods for Targeted Photothermal and Photodynamic Cancer Therapy - Wang, Jian (2012)
An aptamer switch probe (ASP) linking chlorin e6 (Ce6), a photosensitizer molecule, to the surface of gold nanorods (AuNRs) was used to target cancer cells for photodynamic therapy (PDT) and photothermal therapy (PTT). In the presence of target cancer cells, the ASP changes conformation to drive Ce6 away from the gold surface, thereby producing singlet oxygen for PDT upon light irradiation. Since each AuNR is modified with many ASP/Ce6 molecules, the AuNR/ASP/Ce6 conjugate yields enhanced binding and therapeutic effect by the added ability to carry many photosensitizers. In addition, absorption of radiation by the gold nanorods enables further cell destruction by the photothermal effect. Consequently, this multimodal AuNR/ASP/Ce6 conjugate offers a remarkably improved and synergistic therapeutic effect compared to PTT or PDT alone, providing high specificity and therapeutic efficiency, which can be generalized to other types of cancer therapies.